Strategi Meningkatkan Minat Siswa dalam Bermain Tenis Meja di Sekolah - Luwy Bunga Ompusunggu; Maria Siska Sinaga; Meli Marintan Sinambela; Riska Awanda; Muhammad Yan Ahady; Usman Nasution (Journal on Education, 2024)
This study aims to explore effective strategies in increasing students' interest in playing table tennis at school. Through literature study analysis, it was found that the implementation of table tennis extracurricular activities could be an important foundation in attracting student interest. By providing opportunities for students to study and practice regularly, they can begin to develop interest and skills in the sport. In addition, holding tournaments and competitions regularly has also proven effective in providing interesting challenges for students, as well as spurring a competitive spirit that can increase their self-confidence and competitive spirit. Recruiting an experienced and inspiring mentor or coach has also been proven to provide valuable guidance for students in developing their skills. Finally, this research highlights the importance of continuing to develop innovations in school table tennis programs, including experimentation with new training formats, the use of technology for game analysis, and the introduction of creative elements in training to keep student interest high. The implication of these findings is the need for a holistic and integrated approach in increasing students' interest in playing table tennis at school.